2020
DOI: 10.1186/s12885-020-07361-8
|View full text |Cite
|
Sign up to set email alerts
|

MassARRAY-based single nucleotide polymorphism analysis in breast cancer of north Indian population

Abstract: Background Breast Cancer (BC) is associated with inherited gene mutations. High throughput genotyping of BC samples has led to the identification and characterization of biomarkers for the diagnosis of BC. The most common genetic variants studied are SNPs (Single Nucleotide Polymorphisms) that determine susceptibility to an array of diseases thus serving as a potential tool for identifying the underlying causes of breast carcinogenesis. Methods SNP genotyping employing the Agena MassARRAY offers a robust, se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Our results suggested that there was correlation between rs1642742 and metastasis and the allele A might be associated with tumor metastasis. Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on [42–45] . Rs1642742 is residing in the 3′UTR of the VHL , which plays an important role in mRNA translocation, stability and translational regulation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our results suggested that there was correlation between rs1642742 and metastasis and the allele A might be associated with tumor metastasis. Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on [42–45] . Rs1642742 is residing in the 3′UTR of the VHL , which plays an important role in mRNA translocation, stability and translational regulation.…”
Section: Discussionmentioning
confidence: 86%
“…Of course, the correlation between SNP and tumor metastasis had been reported in previous literatures, including lung cancer, breast cancer, gastric cancer, prostate cancer, and so on. [42][43][44][45] Rs1642742 is residing in the 3 0 UTR of the VHL, which plays an important role in mRNA translocation, stability and translational regulation. The variant allele of rs1642742 may affect the ability of miRNA to bind to its sequence, which in turn affects the VHL gene expression and may lead to tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…For SNP genotyping, the Agena MassARRAY platform was used and the whole protocol and conditions were replicated from our previous studies. [ 11,12 ] DNA sample of 1 μl at 10 ng/μl concentration was loaded in 384‐well PCR plates, which was dried at 85°C for 10 min. The reaction mixture consists of dNTPs, primer pool (forward and reverse primers pool) reaction buffers, and DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…11 rs2494752 AKT1 Hepatocellular carcinoma [60] BHAT ET AL. ATM/ATR pathway [63,64] step in exploring genetic factors associated with leukemia, functional studies are now necessary to exemplify the exact biological function of these genes in leukemia for validation. Thus, the study needs to be replicated in the large cohorts for functional validation.…”
Section: Tcf21mentioning
confidence: 99%
See 1 more Smart Citation